2023
DOI: 10.1093/pcp/pcad011
|View full text |Cite
|
Sign up to set email alerts
|

BBX24 Interacts with JAZ3 to Promote Growth by Reducing DELLA Activity in Shade Avoidance

Abstract: Shade avoidance syndrome (SAS) is a strategy of major adaptive significance and typically includes elongation of the stem and petioles, leaf hyponasty, reduced branching, and phototropic orientation of the plant shoot toward canopy gaps. Cryptochrome 1 and phytochrome B (phyB) are both the major photoreceptors that sense the reduction in blue light fluence rate and the low Red:Far-Red (R:FR) ratio, respectively, both light signals associated with plant density and the resource reallocation when SAS responses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The negative interaction between BBX24 and HY5, and its closest homolog HYH, is a common theme in the regulation of seedling photomorphogenesis [17][18][19]22]. In simulated shade, BBX24 can sequester DELLA to promote elongation responses through PIF4 activity [23,24]. More recently, it has been suggested that the module of HY5-BBX24-DELLA can control the crosstalk between GA and UV-B signaling to regulate hypocotyl inhibition [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative interaction between BBX24 and HY5, and its closest homolog HYH, is a common theme in the regulation of seedling photomorphogenesis [17][18][19]22]. In simulated shade, BBX24 can sequester DELLA to promote elongation responses through PIF4 activity [23,24]. More recently, it has been suggested that the module of HY5-BBX24-DELLA can control the crosstalk between GA and UV-B signaling to regulate hypocotyl inhibition [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several BBX proteins have been documented to be involved in seedling de-etiolation, synthesis of anthocyanins, shade avoidance, flowering and responses to abiotic and biotic stresses [13,16]. BBX24 has been documented to inhibit seedling deetiolation [17][18][19][20], repress UVB signaling [21,22] and promote shade avoidance [17,23,24] and flowering [25]. BBX24 was originally isolated as a SALT-TOLERANT (STO) protein in an Arabidopsis cDNA clone screen that conferred increased salt-tolerance in Saccharomyces cerevisiae [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The BBX24 and BBX25 are close homologs that function as transcriptional co-repressors of HY5 to inhibit photomorphogenesis (Gangappa et al, 2013; Job et al, 2018). Additionally, BBX24 functions in various signaling pathways, including UV-B signaling (Jiang et al, 2012; Huang et al, 2022), shade-avoidance response (Crocco et al, 2015b; Saura-Sanchez et al, 2023) and flowering (Li et al, 2014). However, the role of BBX24 and BBX25 in temperature-mediated regulation of growth and development remains unknown.…”
Section: Introductionmentioning
confidence: 99%